2017
DOI: 10.1177/1049732317747554
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Experiences of Supporting Adolescent Children Through Long-Term Treatment for Substance Use Disorder

Abstract: Substance use disorder is a complex phenomenon that affects people in many different contexts. Adolescent substance abuse within families is a particular problem that merits ongoing study. In particular, the experiences of mothers in this context are not fully explored. In this narrative inquiry study, we explored the experiences of four mothers parenting children through long-term substance abuse treatment. Participants were recruited from a family-orientated long-term adolescent treatment center in Alberta, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…The biographical profile of participants reflects that most of them were mothers living in the same household with adolescents misusing nyaope . This correlates with the findings by Smith, Estefan and Caine ( 2018 :512), who reported that because of the pressure on women to be ‘good mothers’, they are compelled to conform to the expected role of being nurturers within the family system. Only two participants were men (fathers) living in the same household with adolescents misusing nyaope .…”
Section: Research Findingssupporting
confidence: 88%
“…The biographical profile of participants reflects that most of them were mothers living in the same household with adolescents misusing nyaope . This correlates with the findings by Smith, Estefan and Caine ( 2018 :512), who reported that because of the pressure on women to be ‘good mothers’, they are compelled to conform to the expected role of being nurturers within the family system. Only two participants were men (fathers) living in the same household with adolescents misusing nyaope .…”
Section: Research Findingssupporting
confidence: 88%
“…There also seems to be a link between substance abuse and mental illness, as many adolescents suffer from mental illness because of substance abuse (Kalam & Mthembu 2018 :468). Parents become angry and disappointed with their adolescents abusing substances, as it destroys the adolescent’s future and the expectations they may have for their child are not met (Smith, Estefan & Caine 2018 :517). Parents may experience stress in looking after adolescents who abuse substance as most of these abusers end up being affected by substance-related mental disorders, which may be experienced as a ‘family burden’.…”
Section: Introduction and Overviewmentioning
confidence: 99%
“…Parents may experience stress in looking after adolescents who abuse substance as most of these abusers end up being affected by substance-related mental disorders, which may be experienced as a ‘family burden’. The majority of problems surrounding adolescent substance abuse have an impact on parents, yet little is known about their experiences (Smith et al 2018 :512).…”
Section: Introduction and Overviewmentioning
confidence: 99%
“…Many of the bereaved mothers in our study spoke of being motivated by tremendous anger and disappointment in the health care system that was supposed to keep their child alive and healthy. Smith et al (2018) alluded to this as the “professional silences” experienced by the mothers in their study who were trying to support their adolescent children being treated for substance use disorder. Therefore, our findings underscore the need for governments and service providers to support a family-centered approach to help individuals who have a loved one struggling with substance use.…”
Section: Discussionmentioning
confidence: 99%